Prospective observational study of dementia and delirium in the acute hospital setting. Issue 3 (27th February 2013) - Travers, C.; Byrne, G.; Pachana, N.; Klein, K.; Gray, L.
Abstract Background Dementia and delirium appear to be common among older patients admitted to acute hospitals, although there are few Australian data regarding these important conditions. Aim The aim of this study was to determine the prevalence and incidence of dementia and delirium among older patients admitted to acute hospitals in Queensland and to profile these patients. Method Prospective observational cohort study (n = 493) of patients aged 70 years and older admitted to general medical, general surgical and orthopaedic wards of four acute hospitals in Queensland between 2008 and 2010. Trained research nurses completed comprehensive geriatric assessments and obtained detailed information about each patient's physical, cognitive and psychosocial functioning using the interRAI Acute Care and other standardised instruments. Nurses also visited patients daily to identify incident delirium. Two physicians independently reviewed patients' medical records and assessments to establish the diagnosis of dementia and/or delirium. Results Overall, 29.4% of patients (n = 145) were considered to have cognitive impairment, including 102 (20.7% of the total) who were considered to have dementia. This rate increased to 47.4% in the oldest patients (aged ≥90 years). The overall prevalence of delirium at admission was 9.7% (23.5% in patients with dementia), and the rate of incident delirium was 7.6% (14.7% in patients with dementia). Conclusion The prevalence of dementia and delirium among older patients admitted to acute hospitals is high and is likely to increase with population aging. It is suggested that hospital design, staffing and processes should be attuned better to meet these patients' needs.